Tool for swine ration for minimum cost (Veterinary Science, 2017)
This article presents the main features of RAC-1, a tool to formulate of least-cost rations for pigs. The tool was developed with Microsoft Excel, Solver subprogram, wich utilizes linear programming
Keywords: Diets; Pigs; Linear programing; Excel